OVERVIEW OF THE STUDENTS' LEARNING INTERESTS OF SMA PERTIWI 1 PADANG - Fauzan Azima; Rezki Hariko; Gusni Dian Suri; Soeci Izzati Adlya (LP2M IAI Al-Khairat Pamekasan, 2026)
stress, and the psychological development of students, if continued, will make the quality of graduates and human resources decrease. The study aims to describe the learning interest in students reviewed from: 1) the affective aspect, 2) the cognition aspect. The research uses a descriptive quantitative method. The number of samples of 230 students of SMA Pertiwi 1 Padang was selected using the stratified random sampling technique. Data collection was carried out through the administration of the student learning interest scale which was compiled based on the Likert scale model. The data was processed using descriptive analysis. The results of the study showed that the learning interest of students of SMA Pertiwi 1 Padang: in general was in the high category (=106.56), from the aspect of affection (feeling) was in the high category and the aspect of cognition (mind) was in the high category. Based on these results, it can be concluded that Pertiwi 1 Padang High School students have a high interest in learning in the learning process. The implication of BK services in increasing students' interest in learning is by providing various services such as information services, individual counseling guidance services and group counseling guidance.